Assessments of in vitro and in vivo antineoplastic potentials of β-sitosterol-loaded PEGylated niosomes against hepatocellular carcinoma. (23rd September 2020) - Nisha, Raquibun; Kumar, Pranesh; Gautam, Anurag Kumar; Bera, Hriday; Bhattacharya, Bolay; Parashar, Poonam; Saraf, Shubhini A.; Saha, Sudipta
Abstract: β-sitosterol (BS), a phytosterol, exhibits ameliorative effects on hepatocellular carcinoma (HCC) due to its antioxidant activities. However, its poor aqueous solubility and negotiated bioavailability and short elimination half-life is a huge limitation for its therapeutic applications. To overcome these two shortcomings, BS-loaded niosomes were made to via, film hydration method and process parameters were optimized using a three-factor Box–Behnken design. The optimized formulation (BSF) was further surface-modified with polyethylene glycol (PEG). The resulting niosomes (BSMF) have spherical shapes, particle sizes, 219.6 ± 1.98 nm with polydispersity index (PDI) and zeta potential of 0.078 ± 0.04 and −19.54 ± 0.19 mV, respectively. The drug loading, entrapment efficiency, and drug release at 24 h of the BSMF were found to be 16.72 ± 0.09%, 78.04 ± 0.92%, and 75.10 ± 3.06%, respectively. Moreover, BSMF showed significantly greater cytotoxic potentials on Hep G2 cells with an enhanced cellular uptake relative to pure BS and BSF. The BSMF also displayed potentially improved curative property of HCC in albino wistar rat. Thus, the BSMF could be one of the promising therapeutic modalities for HCC treatment in terms of targeting potential resulting in enhanced therapeutic efficacy.